Antibacterial and Biofilm Degradation Effects of Hungarian Honeys Linked With Botanical Origin, Antioxidant Capacity and Mineral Content - Farkas, Ágnes; Balázs, Viktória Lilla; Kõszegi, Tamás; Csepregi, Rita; Kerekes, Erika; Horváth, Györgyi; Szabó, Péter; Gaál, Krisztián; Kocsis, Marianna (Frontiers in Nutrition, 2022)
The aim of the study was to assess the impact of four unifloral honeys on the food-borne pathogens Pseudomonas aeruginosa and Staphylococcus aureus, by analyzing the honeys’ antibacterial and biofilm degradation effects, as well as their antioxidant activity and element content. Linden and milkweed honeys represented light colored honeys, while goldenrod and chestnut honeys the darker ones. The botanical origin of the honeys and the relative frequency of their pollen types were established with melissopalynological analysis. The antioxidant capacities were calculated by two single electron transfer based methods (TRC – Total Reducing Capacity and TEAC – Trolox Equivalent Antioxidant Capacity) and a hydrogen atom transfer based assay (ORAC – Oxygen Radical Absorbance). The amount of four main macro- and two microelements was quantified. The antibacterial activity was determined by minimum inhibitory concentration (MIC) and membrane degradation assays. Furthermore, the biofilm degradation power of the samples was studied as well. The light colored linden honey with the lowest TRC and TEAC, but with the highest ORAC antioxidant activity and high element content showed the best antibacterial and biofilm degradation effects. Meanwhile, the dark colored chestnut honey with significantly higher single electron transfer based antioxidant capacities, with high element content, but lower ORAC showed significantly higher MIC and lower membrane degradation activity than linden honey. In case of biofilm degradation, both honey types gave similarly high inhibitory effect. Goldenrod honey was similarly effective regarding its MIC properties like chestnut honey, but had significantly lower antioxidant potential and ability to disrupt bacterial membranes and biofilms. Milkweed honey was the honey type with the lowest bioactivity and element content. The honeys, unequivocally characterized by their antioxidant characters and element content, displayed different antibacterial and biofilm degradation effects. In addition, some honey traits were found to be good predictors of the antimicrobial potential of honeys: ORAC assay showed correlation with the MIC values of both bacteria, and strict correlation was found between the mineral content and the antibiofilm activity of the studied honeys. Our studies indicate that unifloral honeys, such as linden and chestnut honeys, are plant-derived products with great potential as antimicrobial agents in food preservation, exhibiting remarkable antibacterial activity against food-borne pathogens.